Iran is falling behind WHO cervical cancer elimination targets: HPV vaccination coverage and cervical cancer screening participation in 2021 - Mohammad Haddadi; Ali Golestani; Yosef Farzi; Nazila Rezaei; Erfan Ghasemi; Sina Azadnajafabad; Negar Rezaei; Naser Ahmadi; Mohammad-Mahdi Rashidi; Maryam Nasserinejad; Ameneh Kazemi; Moein Yoosefi; et al. (PLoS ONE, 2026)
Objective This study aimed to assess HPV vaccination coverage and cervical cancer screening participation among Iranian females under 46 years old, comparing Iran’s situation to he Cervical Cancer Elimination Initiative (CCEI) targets. Methods This nationally and sub-nationally representative cross-sectional study analyzed data from the STEPS 2021 survey. Female participants aged 18–45 years without missing data on HPV vaccination or cervical cancer screening were included. Categorical data were presented as weighted percentages with 95% confidence intervals (95% CI). Logistic regression assessed associations between demographic and female cancer screening variables with the outcomes. Results A total of 8,158 females were included. Only 0.85% (95% CI: 0.69–1.02) of women received the HPV vaccine, while cervical cancer screening participation was 39.4% (95% CI: 38.21–40.6). No significant differences in HPV vaccination coverage were observed across age groups. However, screening rates were significantly higher in older women, rising from 27.99% (18–35 years) to 54.07% (36–45 years). HPV vaccination was not significantly associated with demographic variables. In contrast, cervical cancer screening participation was higher among unemployed women (40.58%), married women (49.6%), and those in the highest wealth quintile (42.47% compared to 28.29% in the lowest quintile). Conclusion HPV vaccination coverage in Iran is critically low, falling far short of the CCEI target of 90%. Cervical cancer screening participation is comparatively better but still lags approximately 30% behind the target. Strategic interventions are critical to bridge the gap between Iran’s current status and the CCEI targets.